Dation in payment in Civil and Commercial Code - Moro, Emilio F. (Universidad Nacional del Litoral, 2020)
In this work we analyze how the Argentine Civil and Commercial Code, since his entry into force five years ago, has addressed in a wise and reasonably way the dation in payment (datio in solutum), improving the legislative technique of the previous Code on this matter.